2022
DOI: 10.1186/s40959-022-00149-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors and the risk of major atherosclerotic cardiovascular events in patients with high-risk or advanced melanoma: a retrospective cohort study

Abstract: Background Immune checkpoint inhibitors (ICI) are associated with immune-mediated adverse effects, potentially involving any organ. ICI has also been associated with an increased risk of cardiovascular disease in cancer populations. Objective To characterize the incidence and risk of major atherosclerotic cardiovascular events associated with ICI use in a high-risk and advanced melanoma population. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…For example, Drobni et al [ 14 ] found that the risk of myocardial infarction, coronary revascularization, and ischemic stroke increased at varying degrees after the use of ICIs, and that total aortic plaque volume also showed a simultaneous increase. Similar findings were found in the melanoma patient cohort studied by Wang et al [ 15 ]. In the study by Schiffer et al [ 16 ], patients treated with ICIs who had cardiovascular events had worse baseline coronary and aortic calcification.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Drobni et al [ 14 ] found that the risk of myocardial infarction, coronary revascularization, and ischemic stroke increased at varying degrees after the use of ICIs, and that total aortic plaque volume also showed a simultaneous increase. Similar findings were found in the melanoma patient cohort studied by Wang et al [ 15 ]. In the study by Schiffer et al [ 16 ], patients treated with ICIs who had cardiovascular events had worse baseline coronary and aortic calcification.…”
Section: Introductionsupporting
confidence: 90%
“…In 2020, Drobni et al [ 14 ] first reported that ICIs were highly associated with atherosclerotic cardiovascular events. Recently, Wang et al [ 15 ] found an increased risk of ASCVD events in patients with high-risk or advanced melanoma after ICI therapy. Similar conclusions have been reached in a cohort of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…In the OSs, our results show that ICI use was not associated with increased risk of myocarditis ( P =0.09) or pericardial disease ( P =0.19, Figure 6 , 14 , 17 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ). However, the use of combination ICIs was associated with higher risk of myocarditis (OR, 3.07 [95% CI, =1.28–7.39], P <0.02) but not pericardial disease (OR, 4.13 [95% CI, 0.19–89.86], P <0.67) compared with single ICI therapy in OSs.…”
Section: Resultsmentioning
confidence: 71%
“… Forest plot of included OSs, separated based on therapy comparisons for myocarditis 14 , 17 , 53 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ( A ) and pericardial disease 17 , 53 , 54 , 55 , 56 ( B ). The squares and horizontal lines correspond to the study‐specific ORs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials have shown that monoclonal antibodies targeting these molecules can improve outcomes for patients with cardiovascular diseases. Adoptive cell transfer involves the transfer of immune cells that have been genetically engineered to target specific disease-causing agents [131]. For example, T cells can be engineered to target and destroy cells that contribute to atherosclerosis.…”
Section: Some Examples Of Immunotherapy Approaches For Cardiovascular...mentioning
confidence: 99%